Taxonomic notes on three species of Tiwaripotamon Bott, 1970 (Crustacea: Brachyura: Potamidae) from Vietnam and China, one of which is new to science - Ng, Peter K. L. (Zootaxa, 2024)
A new species of semiterrestrial freshwater crab, Tiwaripotamon nganima n. sp. is described from northern Vietnam. The gonopods of the new species most closely resemble T. annamense (Balss, 1914) originally collected from Phuc-Son in Annam, central Vietnam, but can easily be distinguished as it has the median lobe on the posterior margin of the epistome being more projecting, the male pleon is proportionately more quadrate and less wide, the basal part of the male first gonopod has the median part of the subterminal segment more strongly curved, and the outer surface of the basal part of the terminal segment of the male first gonopod is prominently swollen. The taxonomy of two species described from southern China, T. pingguoense Dai & Naiyanetr, 1994, and T. xiurenense Dai & Naiyanetr, 1994, is also clarified after re-examination of type specimens and photographs of the original material; both species are redescribed and refigured.